DRIP IRRIGATION REGIMES AND FERTIGATION LEVELS INFLUENCE ON YIELD AND YIELD ATTRIBUTES OF Bt COTTON - V. PRAVEEN RAO, K. MARK GLADSTON, K. AVIL KUMAR and (The Journal of Research, PJTSAU, 2017)
Cotton, the king of natural fibre is the natures gift to mankind and in India it is mostly grown as rainfed and under furrow irrigation being a row crop.As water is limiting for crop production due to ever increasing competition among different sectors, there is a need for increasing the water use efficiency by producing more crop per drop. Adoption of drip irrigation is one way of increasing the water use efficiency with high irrigation efficiency. Water saving of 30-60 per cent could be possible compared to furrow irrigation since, only active root zone is wetted under drip irrigation. To achieve full potential of microirrigation, fertigation is not optional but mandate (Sivanappan, 2004). Fully water soluble fertilizers can be injected via micro irrigation to supply N, P and K in one solution directly to the root zone of the crops. The information on response of Bt cotton for drip irrigation as well as fertigation is meager in Telangana. Hence an experiment was planned to study the influence of fertigation levels and drip irrigation regimes on yield and yield attributes of Bt cotton.